The Role of Spirituality in Pasifika/Pacific Mental Health: A Scoping Review - Kaipo, Allana (Auckland University of Technology, 2022)
Mental health continues to be an increasing concern among Pasifika/Pacific peoples. The general lack of cultural and spiritual competency among mental health practitioners remains a barrier for Pasifika/Pacific individuals and families in accessing services. Pasifika/Pacific worldviews tend to be different from the dominant Western health perspectives, and Pasifika/Pacific people therefore seem to be underrepresented in the mental health workforce. Through the use of a scoping literature review methodology, this review explored how the role of spirituality in Pasifika/Pacific mental health is discussed and reported in the academic literature. A total of 2478 online articles were identified, and 19 met the criteria to be included in the final review. Using content analysis, the data revealed four overarching themes: Understanding Mental Health in the Spiritual Context, Spiritual Causes of Mental Illness/Distress, Spiritual Coping from Mental Illness/Distress, and Spiritual Practices for Healing Mental Illness/Distress. The scoping literature review found that the role of spirituality is primarily understood within traditional constructions, including tapu and sacred relationships, and/or Christian constructions of wellness. Within traditional constructions, spiritual curses and possession were found to be key causes of mental illness/distress as a result of breaching tapu and sacred relationships, as well as healing practices; whilst Christian orientations of spirituality were found to provide effective coping and intervention strategies. The review emphasises the necessity of attending to spiritual relationships with God, people and the land/environment, keeping them in balance to achieve mental wellness. Viewing the Pasifika/Pacific individual as a relational, spiritual and holistic being is also essential for effective mental health interventions. As this study looked at Pasifika/Pacific groups as a whole, further research in this area would benefit from exploring Pasifika/Pacific spirituality from an ethnic specific point of view. This would allow for a more thorough understanding of mental health constructions that would contribute to a more personalised approach to mental health services for Pasifika/Pacific service users.